A counseling framework addressing the risks and vulnerabilities of women in prostitution - Zamar, Mildred; Ho, Leticia P.; de Guzman, Ligaya S.; Sobritchea, Carolyn I. (Quezon City College of Education, University of the Philippines Diliman, 2012)
There is an increasing rate of HIV and AIDS cases in the country which is an alarming concern even to the marginalized group such as Women in Prostitution (WIP). To address this said reality, this research looked into the perception of WIP, pimps and health educators on HIV and AIDS in terms of its definition, risks, prevention and testing. It also looked at ways on how to address the risks and vulnerabilities of WIP to HIV/AIDS. lastly, this study developed a counseling framework to deal with WIP's risks and vulnerabilities. The outcome of this study showed that WIP have misconceptions on HIV/AIDS either because they lack or have no knowledge of them. It also showed that a holistic approach to empowerment is needed to address WIP's risks and vulnerabilities to HIV/AIDS. Thus, counseling framework was developed to identify the short and long term counseling interventions to deal with these problems.
Thesis (M.A. Education-Guidance)--University of the Philippines, Diliman.
Keywords: Prostitution -- Philippines -- Quezon City; AIDS (Disease) -- Philippines -- Quezon City; HIV infections -- Philippines -- Quezon City; Prostitutes -- Counseling of -- Philippines -- Quezon City